Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Dinas Kependudukan dan Pencatatan Sipil Kota Serang - Ende Ende; Ahmad Asep Firdaus (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This Research aims to determine the influence of the work environment on the performance of employees who are mediated by job satisfaction at the population Office and civil registration of Serang City. Sampling is done by non-probability samplingi.e. the saturated sample (census). The number of samples used in this study was as much as 61 employees. In this study, these three variables were analyzed using a simple linear regression analysis through the significance test with the SPSS program. The object of this research is all officers of the population Service and civil registration of Serang City. The results of the study showed that the working environment was influential in the performance of the population service and civil registration of Serang. Hypothesis 1 is supported, the working environment affects the performance of the Population Service officers and civil registration of Serang City. Hypothesis 2 is supported, the working environment affects the work satisfaction of the population service and civil registration of Serang City. Hypothesis 3 is supported, job satisfaction affects the performance of the Population Service officers and civil registration of Serang City. In addition, research results show that the working environment affects employees ' performance by being mediated by work satisfaction at the population office and the civil registration of Serang City thus 4 hypotheses are supported.